Aberrant hepatic arteries running through pancreatic parenchyma encountered during pancreatoduodenectomy: Two rare case reports and strategies for surgical treatment. Issue 49 (December 2016) - Wang, Lei; Xu, Jianwei; Sun, Dong; Zhang, Zongli
Abstract: Background: Aberrant hepatic arteries (HAs) encountered during pancreatoduodenectomy are difficult to manage. Mehtods: Two cases with rare types of aberrant HA running through the pancreatic parenchyma were reviewed. Results: The first case, a 68-year-old man, was admitted with obstructive jaundice. A tumor of the pancreatic head and aberrant HAs were suspected on computed tomography (CT) scan. At laparotomy, a new variation was identified; namely, 2 aberrant arteries—a right replaced HA and middle HA (RMHA) that both originated from the superior mesenteric artery (SMA) and ran via intrapancreatic paths posterior and anterior to the pancreatic head, respectively. Branches of the RMHA to the pancreas were ligated and severed and the trunk preserved. The RMHA was mistakenly identified as an aberrant left HA (RLHA), whereas the RLHA was overlooked and not dissected intraoperatively. CT angiography performed 11 days postoperatively identified that the RLHA originated from the left gastric artery (LGA). The second case had a variation of Michels IX. A 58-year-old woman presented with obstructive jaundice and a distal cholangiocarcinoma was suspected on the basis of enhanced CT scan. At laparotomy, the common hepatic artery (CHA) was found to originate entirely from the SMA and run posterior to the pancreatic head via an intrapancreatic path. The segment of CHA in the pancreatic parenchyma was removed and reconstructed with the LGA. Conclusions: Preoperative identification of aberrant HAs helps in planning appropriate operative procedures and minimizing unnecessary complications. Both preservation and reconstruction of these arteries are technically safe and feasible; however, preservation is preferable. Abstract : Supplemental Digital Content is available in the text